Konkurs Sienkiewiczowski 2016 – refleksje po sukcesie - Czarnik, Mirosław (Dydaktyka Polonistyczna, 2017)
The articles deals with the methods of working with a talented student during preparations forcontests and competitions. This is not a guide explaining, step by step, the methodology of preparations for contests and competitions. The author concentrates on reflections based upon experienceand emphasizes the importance of correlation between a student and a teacher, and a student anda school. The article also includes Agata Froń’s essay awarded in Konkurs Sienkiewiczowski in 2016.Agata Froń is a student of Liceum Ogólnokształcące w Strzyżowie.